Effect of Human Corneal Mesenchymal Stromal Cell-derived Exosomes on Corneal Epithelial Wound Healing - Samaeekia, Ravand; Rabiee, Behnam; Putra, Ilham; Shen, Xiang; Park, Young Jae; Hematti, Peiman; Eslani, Medi; Djalilian, Ali R. (Investigative ophthalmology & visual science, 2018)
Mesenchymal stromal cells (MSCs) have been used therapeutically to modulate inflammation and promote repair. Extracellular vesicles, including exosomes, have been identified as one of the important mediators. This study investigated the effect of human corneal MSC-derived exosomes on corneal epithelial wound healing. Corneal MSCs (cMSCs) were isolated from human cadaver corneas. The secretome was collected after 72 hours and exosomes were isolated using differential ultracentrifugation. Morphology and size of exosomes were examined by electron microscopy and dynamic light scattering. Expression of CD9, CD63, and CD81 by cMSC exosomes was evaluated by western blotting. Cellular uptake of exosomes was studied using calcein-stained exosomes. The effect of exosome on wound healing was measured in vitro using a scratch assay and in vivo after 2-mm epithelial debridement wounds in mice. cMSC exosomes were morphologically round and main population ranged between 40 and 100 nm in diameter. They expressed CD9, CD63, and CD81, and did not express GM130, Calnexin, and Cytochrome-C. Stained cMSC exosomes were successfully taken up by human cMSCs, human corneal epithelial cells (HCECs), and human macrophages in vitro and by corneal epithelium in vivo. In scratch assay, after 16 hours, cMSC exosome treated HCECs had 30.1% ± 14% remaining wound area compared to 72.9% ± 8% in control (P < 0.005). In vivo, after 72 hours, cMSC exosome-treated corneas had 77.5% ± 3% corneal wound healing compared to 41.6% ± 7% in the control group (P < 0.05). Human cMSC exosomes can accelerate corneal epithelial wound healing, and thus, may provide a therapeutic approach for ocular surface injuries.